Analisis Faktor – Faktor Yang Mempengaruhi TPAK Aceh Dalam Jangka Panjang Dan Jangka Pendek - Fajar Aulia Ramadhan; Devi Andriyani (JURNAL EKONOMIKA INDONESIA, 2023)
This study aims to determine the relationship between the provincial minimum wage, average length of schooling, inflation, population and labor force participation rate in Aceh Province in 2006 – 2020. This research uses secondary data for 15 years. This study used the Autoregressive Distributed Lag (ARDL) test analysis method. The results of this study show that in short-term testing the provincial minimum wage variables, average length of schooling, and population have a positive but not significant effect on the labor force participation rate and the inflation variable has a negative but not significant effect on the labor force participation rate. Meanwhile, in the long term, the provincial minimum wage, average length of schooling, and population have a positive but not significant effect on the labor force participation rate and the inflation variable has a negative but not significant effect on the labor force participation rate